The lizard genus phenacosaurus (1944)
Examination of 64 specimens of this endemic Colombian genus in the collections of the Instituto de Ciencias Naturales, the Instituto de La Salle in Bogotá, and the Colegio San José in Medellin indicates that the genus is not monotypic but is composed of at least three species. The genus Phenacosaurus was described by Barbour in 1920 (Proc. New England Zool Club, 7, pp. 61-63) with Anolis heterodermus Duméril as the monotype. The genus is close to Anolis, being distinguished by having a prehensile tail, a dorsal crest of enlarged scales, heterogeneous dorsal scalation of larger and smaller scales intermixed, and by having more or less of a casque, the hind end of the head being elevated and projecting backward somewhat over the body. Anolis jacare, of Norte de Santander and adjacent Venezuela, may be close to the parent stock of Phenacosaurus.